2006
DOI: 10.1111/j.1745-4573.2006.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PREDICTION OF FAT PERCENTAGE IN THE LONGISSIMUS DORSI MUSCLE IN FED BEEF USING NUCLEAR MAGNETIC RESONANCE

Abstract: The objective of this study was to develop predictive equations to estimate the percentage of crude fat in beef longissimus dorsi muscles from subjective marbling evaluations or objective visual evaluations. Forty beef ribs and loins representing four U.S. Department of Agriculture (USDA) quality grades – USDA Prime (n = 10); USDA Premium Choice [upper 2/3 of Choice] (n = 10); USDA Low Choice (n = 10); and USDA Select (n = 10) – were fabricated into 3.17‐cm transverse slices for subjective and objective visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Moore et al (2010) also reported an increase in fat percentage variance as marbling score increased and that both expert panel graders and camera grading precision decreased as marbling score increased. Garcia et al (2006) found similar results of variation in fat percentage using the CEM.…”
Section: Prediction Equations For Fat Determination Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…Moore et al (2010) also reported an increase in fat percentage variance as marbling score increased and that both expert panel graders and camera grading precision decreased as marbling score increased. Garcia et al (2006) found similar results of variation in fat percentage using the CEM.…”
Section: Prediction Equations For Fat Determination Methodssupporting
confidence: 67%
“…Compared with Moore et al (2010), means for ether-extractable fat in this study were numerically greater for SLAB, MD, and SL and less for MT and SM. Garcia et al (2006) reported the same relative relationships using microwave drying and NMR with the CEM SMART Trac for determining percentage of fat within LM. Means for CEM fat were numerically less for all marbling levels in this study compared with Garcia et al (2006), which may be due to sample size differences.…”
Section: Crude Fatmentioning
confidence: 87%
See 1 more Smart Citation
“…In the same context of non-destructive evaluation, few works have been identified in the literature [13,14]. This could be due to the nature of the problem which is both recent and complex.…”
Section: Introductionmentioning
confidence: 99%
“…The range of the volumetric marbling of the meat samples is estimated at 9 to 27 % of the volumetric meat sample. Garcia et al [11] predicted the percentage of intramuscular fat in beef Longissimus dorsi muscle classified as "Prime" with respect to the U.S Department of Agriculture (USDA) grading system [11], which is equivalent to AAA grade in Canada. In this study, the predicted minimum and maximum values of marbling ranged between 7.09 and 18.32%, which demonstrates that our estimation is in accordance with the recognized grading system.…”
Section: Resultsmentioning
confidence: 99%